2011
DOI: 10.1002/ijc.25461
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated epigenetic repression of the miR‐200 family and miR‐205 in invasive bladder cancer

Abstract: MicroRNAs (miRNA) are small noncoding RNAs commonly deregulated in cancer. The miR-200 family (miR-200a, -200b, -200c, -141 and -429) MicroRNAs (miRNA) are a class of $22nt noncoding RNAs that regulate gene expression post-transcriptionally.1 It is widely accepted that miRNA expression is broadly altered in most forms of cancer, 2 and loss of miR-200 family (miR200a, -200b, -200c, -141 and-429) expression has been reported in several types of advanced carcinoma, including bladder cancer. 3,4 Recently, seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
264
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(293 citation statements)
references
References 31 publications
22
264
1
2
Order By: Relevance
“…It has been suggested that the tumorsuppressive function of miR-205 takes place through counteracting epithelial-to-mesenchymal transition and reducing cell migration and invasion in the human prostate (Gandellini et al, 2009;Majid et al, 2010). K27me3 modifications of the miR-205 locus was reported to occur in the PCa cell line PC3 (Ke et al, 2009) and in muscle-invasive bladder tumors and undifferentiated bladder cell lines (Wiklund et al, 2010). These findings, together with the early loss of miR-205 during PCa progression observed by us and others (Porkka et al, 2007;Ambs et al, 2008;Schaefer et al, 2010) present miR-205 as an attractive diagnostic marker for PCa disease.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the tumorsuppressive function of miR-205 takes place through counteracting epithelial-to-mesenchymal transition and reducing cell migration and invasion in the human prostate (Gandellini et al, 2009;Majid et al, 2010). K27me3 modifications of the miR-205 locus was reported to occur in the PCa cell line PC3 (Ke et al, 2009) and in muscle-invasive bladder tumors and undifferentiated bladder cell lines (Wiklund et al, 2010). These findings, together with the early loss of miR-205 during PCa progression observed by us and others (Porkka et al, 2007;Ambs et al, 2008;Schaefer et al, 2010) present miR-205 as an attractive diagnostic marker for PCa disease.…”
Section: Discussionmentioning
confidence: 99%
“…ZEB1 and ZEB2 are regulated by members of the miR-200 family and miR-205 161 . miR-200 is downregulated in bladder cancer cell lines with mesenchymal phenotype and epigenetic silencing is reported in MIBC 162 .…”
Section: Emt and Metastasismentioning
confidence: 99%
“…Previous reports showed that miR-200 family members were downregulated in many tumors, including breast, pancreatic and bladder cancers because of hypermethylation of the miR-200 promoter Neves et al, 2010;Vrba et al, 2010;Wiklund et al, 2011). To test whether the downregulation of miR-200 family members in SNU484-LPCX cells resulted from miR-200 promoter hypermethylation, we treated SNU484-LPCX cells with 5-aza-2 0 -deoxycytidine.…”
Section: Regulation Of the Mir-200 Promoter By Smad3mentioning
confidence: 99%